Design and Realization of LNA Prototype Frequency 1090 Mhz for ADS-B on Nano Satellite - Desio Hasbin Dafiq; Erfansyah Ali; E Edwar; Shindy Atila Putri (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2021)
The nanosatellite is a satellite with a weight of less than 10kg and an orbital height of 500km. Telkom University through Nano Satellite Laboratory is researching for many payloads on a nanosatellite. One of the nanosatellite payloads is Automatic Dependence Surveillance-Broadcast (ADS-B), an aircraft data transmission broadcast. The long-distance deliveries and space environmental disturbances can cause weak received signals. Therefore a Low Noise Amplifier (LNA) is needed to enhance the signal-to-noise ratio (SNR) of a received signal. This paper has successfully designed and prototyped a single-stage LNA with a gain of 12.7dB and it enhances coverage of ADS-B from 180 to 358km